To Cut or Not to Cut: Physicians’ Perspectives on Referring Adolescents for Bariatric Surgery - Woolford, Susan J. (2010)
BACKGROUND: As the prevalence and severity of obesity among adolescents has increased, so has the number seeking bariatric surgery. Little is known about the opinions and referral behaviors of primary care physicians regarding bariatric surgery among adolescents. Therefore, the objective of this study was to assess primary care physicians’ opinions regarding referral of obese adolescents for bariatric surgery. METHODS: In spring of 2007, a two-page survey was fielded to a national randomsample of physicians (375 pediatricians and 375 family physicians). The survey explored physicians’ opinions about: (1) whether they would ever refer an adolescent for bariatric surgery, (2) the minimum age at which bariatric surgery should be considered, and (3) prerequisites to bariatric surgery. Chi-square tests were used to examine associations in responses. RESULTS: The response rate was 67%. Nearly one-half of physicians (48%) would not ever refer an obese adolescent for bariatric surgery. The most frequently endorsed minimum age at which physicians would make a referral for bariatric surgery was 18 years (46%). Almost all respondents endorsed the need for participation in a monitored weight management program prior to bariatric surgery (99%). However, the recommended duration of treatment varied from 3 months to over 5 years, with almost half recommending 12 months of monitored treatment prior to surgery. CONCLUSION: Some severely obese adolescents may desire and potentially benefit from bariatric surgery, but referral for the procedure may depend heavily on the attitudes of their primary care physicians.